Mediterranean diet and atrial fibrillation: a case-control study from China - Zhang, Qian; Wu, Su-Ping; Liu, Xu; Wang, Yun-Long (Frontiers in Nutrition, 2024)
The aim of this study was to assess the association between adherence to Mediterranean diet and the presence of atrial fibrillation (AF) in a Northern Chinese population.This study was a single center, case-control study. A total of 952 low risk participants in Beijing Anzhen Hospital from 2016 to 2021 were collected, including 476 patients with first diagnosed of atrial fibrillation and 476 age and sex matched controls.According to the food frequency questionnaire (FFQ), the alternate Mediterranean diet score (AMED) was calculated, which was 0-9 points，indicating the adherence to the Mediterranean diet from low to high.The average age of the participants was 57.6±9.1 years old, and 70.2% were men.After analyzing every component of AMED, vegetable consumption shows a negative correlation with the risk of AF, whereas alcohol consumption demonstrates a positive correlation with it (OR=0.61, 95% CI 0.44-0.80, P<0.001; OR=1.99, 95% CI 1.48-2.58, P<0.001). All patients were grouped according to AMED score. A significant inverse association between AMED and the risk of AF was observed. Compared with participants with AMED<4, the multivariable-adjusted ORs of AF were 0.75 (95% CI 0.55-1.06) for AMED 4-5 and 0.61 (95% CI 0.43-0.89) for AMED ≥6, with a trend in risk (P=0.008). Results were consistent in stratified analyses of gender, age, BMI and smoking.The Mediterranean diet was inversely associated with the risk of AF in this Northern Chinese population.